A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
History; Religious Studies
Keywords: Great Transformation; The (Book); KING; Martin Luther; Poor People's Campaign; TRUMP; Donald; embeddedness

Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation - Davy, Barbara Jane; Quilley, Stephen (Journal for the Study of Religion, Nature & Culture, 2018)
Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.
Environmental Studies; Religion Studies
Keywords: POLANYI; Karl; 1886-1964; animism; ecological conscience formation; ecology - religious aspects; environmental behaviour; gift economy; informal governance; new animism; ontology; relational ontology; religion and ecology; ritual; systems theory; systems thinking

The moral economy of the Didache - Draper, Jonathan A. (Hervormde Teologiese Studies, 2011)
This article applies the model of the moral economy in the ancient world, as formulated by Karl Polanyi and applied by Halvor Moxnes, to the economic relations reflected in the Didache. The study partly confirms Aaron Milavec's contention that the instructions in the text would provide an 'economic safety net' for members of the community by putting in place a system of generalised reciprocity and redistribution, although Milavec's depiction of the community as an 'urban working class' movement is found to be anachronistic. The 'communion of the saints' is very much an economic system with aspects of resistance to the Roman imperial system. However, the moral economy of the Didache is seen to reflect a number of ambiguities, particularly in its adoption of the Christian Housetable ethic but also in its adoption of the patron client terminology in the dispute between prophets and teachers on the one side and bishops and deacons on the other.
Religion Studies; Theology
Keywords: Bible; Bible - terminology; Bible - theology; Christian ethics; MILAVEC; Aaron; ambiguity; economic systems; moral economy; theology

Karl Polanyi, Marshall Sahlins, and the Study of Ancient Social Relations - Kirk, Alan (Journal of Biblical Literature, 2007)
Questions arise whenever social-scientific models are used in analysis of ancient texts, particularly regarding the feasibility of their application to social and cultural milieux different from those from which they were derived. An essay I authored that assessed the command in Luke 6 to "love your enemies" from the perspective of ancient reciprocity ethics, and that invoked Marshall Sahlins's taxonomy of reciprocity relations (general, balanced, and negative reciprocity), was queried by Zeba Crook on precisely this point, namely, whether it applied Sahlins's taxonomy to Greco-Roman reciprocity relations without adequate attention to the distinctions between kinship organized tribal societies (the focus of Sahlins's analysis) and the socially stratified agrarian societies characteristic of the ancient Mediterranean world.1 Crook's piece was more than just a critique on that point; it raised questions about the extent to which Sahlins's model has applicability to the Roman world. This essay will focus on this key point and, it is hoped, will also contribute to the discussion on the use of social-scientific research in biblical studies.
Religion Studies; Philosophy
Keywords: SAHLINS; Marshall; biblical studies; clientelism; cognitive models; economic models; kinship; reciprocity; slave trade; social interaction; stone age

Religion and the Market: Opposition, Absorption, or Ambiguity? - Haddorff, David W. (Review of Social Economy, 2000)
This article addressed the complex relationship between religion and the market by proposing three basic paradigms, and then applying them to contemporary Christian social thought (or social ethics). The first conflicting model, following Max Weber and Karl Marx, views religion and the market in opposition, which results in greater secularisation. The second, following Emile Durkheim, proposes a 'functionalist' model of society, in which the market itself becomes sacred. The third, following Karl Polanyi, claims the two are more dialectical, in that both are affected by the power of the other; they remain in an ambiguous relationship. The author argues that the third model is the most coherent description of this complex relationship as well as the one most consistent with the convictions of Chrstian social thought.
Religion Studies; Theology
Keywords: church & state; dialectical; double movement; dystopian; economics; functionalism; hom. economics; homo economicus; religious aspects; secularisation; secularization; social ethics